Digital Transformation of UMKM Nusantria: Enhancing Batik and Ecoprint Marketing through Social Media and E-Commerce in Wonosalam - Aileena Solicitor C.R.E.C; Mahimma Romadhona; Roziana Febrianita (Jurnal Abdimas Indonesia, 2025)
This study examines the 2025 community service program aimed at transforming the digital marketing capabilities of UMKM Nusantria, a batik and ecoprint MSME in Sumberjo Village, Wonosalam Subdistrict, Jombang Regency, East Java. Addressing challenges in digital marketing skills, content management, and market access, the program employed a Community-Based Empowerment scheme, providing training, content production tools (lighting studios, mini studios, gimbals), and a dedicated website. Qualitative evaluation through interviews, observations, and screenshots revealed enhanced Instagram engagement, active Shopee content with customer purchases, and improved content management skills, aligning with SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure). Dissemination via workshops, UPN Veteran Jatim’s portal, and case studies positioned UMKM Nusantria as a replicable model for East Java’s creative economy. Future initiatives could integrate advanced SEO training and cooperative models to further expand market reach, fostering sustainable growth in Indonesia’s MSME sector.